'LA05006', a Dual‐Purpose Oat for Louisiana and Other Southeastern Regions of the USA. Issue 2 (27th April 2017) - Harrison, S. A.; Babar, M. A.; Barnett, R. D.; Blount, A. R.; Johnson, J. W.; Mergoum, M.; Mason, E.; Murphy, J. P.; Simoneaux, B.; Ibrahim, A. M. H.
Abstract : 'LA05006' (Reg. No. CV‐382, PI 678581), a winter‐type, dual‐purpose oat ( Avena sativa L.) suited for grain and forage production, was codeveloped by Louisiana State University Agricultural Center and the University of Florida and was released in 2012 under the SunGrains cooperative small grain breeding program among six southeastern universities. Exclusive marketing rights were licensed to Plantation Seed Conditioner, Newton, GA, for sales under the name 'Horizon 306'. This line was derived from a single cross, 'Plot Spike LA9339'/'TAMO 405', and was' tested as LA05006GSBS‐65‐S1. LA05006 was developed using a selected bulk breeding method and was selected as an F5:6 head row. It was evaluated in preliminary, advanced, regional, and state grain and forage yield trials from 2010 to 2012. It is a midmaturing, medium to midtall oat with excellent forage yield and very good grain yield and test weight and also demonstrates excellent lodging resistance. LA05006 was observed to be uniform and stable from 2010 to present. It possesses a semiprostrate winter growth habit and has large leaves that are dark green in color. LA05006 is resistant to stem rust and has shown good resistance to crown rust. Average winter and spring forage yield of LA05006 was slightly higher than other popular dual‐purpose winter oat cultivars ('Horizon 201', 'Horizon 270', and Plot Spike LA9339) and was similar to 'LA99016'. LA05006 has broad environmental adaptation and has performed well in Louisiana, Florida, Georgia, Texas, and Mississippi.